A single oncogenic enhancer rearrangement causes concomitant EVI1 and GATA2 deregulation in leukemia - Gröschel, Stefan; Sanders, Mathijs A; Hoogenboezem, Remco; de Wit, Elzo; Bouwman, Britta A M; Erpelinck, Claudia; van der Velden, Vincent H J; Havermans, Marije; Avellino, Roberto; van Lom, Kirsten; Rombouts, Elwin J; van Duin, Mark; et al. (Cell, 2014)
Chromosomal rearrangements without gene fusions have been implicated in leukemogenesis by causing deregulation of proto-oncogenes via relocation of cryptic regulatory DNA elements. AML with inv(3)/t(3;3) is associated with aberrant expression of the stem-cell regulator EVI1. Applying functional genomics and genome-engineering, we demonstrate that both 3q rearrangements reposition a distal GATA2 enhancer to ectopically activate EVI1 and simultaneously confer GATA2 functional haploinsufficiency, previously identified as the cause of sporadic familial AML/MDS and MonoMac/Emberger syndromes. Genomic excision of the ectopic enhancer restored EVI1 silencing and led to growth inhibition and differentiation of AML cells, which could be replicated by pharmacologic BET inhibition. Our data show that structural rearrangements involving the chromosomal repositioning of a single enhancer can cause deregulation of two unrelated distal genes, with cancer as the outcome.